The Early Grade Reading Assessment Applications and interventions to improve basic literacy - Gove, Amber; Wetterberg, Anna (RTI Press Publication, 2011)
The Early Grade Reading Assessment (EGRA) measures students' progress towards reading. EGRA gauges early literacy skills through a 15-minute individual oral assessment of five fundamental reading skills. RTI worked with education experts to develop the EGRA in 2006, and it has been piloted and implemented in more than 40 countries. This volume aims to take stock of the substantial amount of information and experience generated through the use of EGRA, and to share this knowledge with practitioners, policymakers, and international donors. Chapters cover not only particular applications of the instrument but also put EGRA in the context of broader issues and developments in literacy and education.